Allegorization of History in Burial at Sea - Adhikari, Tara Prasad (International Research Journal of MMC, 2024)
The paper titled “Allegorization of History in Burial at Sea” investigates Khushwant Singh's novel as an allegorized history of post-independent India. Published in 2005, Singh's narrative intertwines the lives of fictional characters with historical figures. Using a combination of textual analysis and historical data, this study examines how Singh's portrayal of these characters serves as an allegorical representation of broader historical narratives. By analyzing the allegorical elements within the novel, the study reveals how Singh's fictionalization serves to critique the idealized images of prominent historical figures, such as Jawaharlal Nehru, and the socio-political dynamics of their time. The findings suggest that Singh's work offers a complex re-interpretation of historical events and figures, highlighting the intersection of fiction and history. The significance of this study lies in its contribution to the discourse on the allegorical nature of historical fiction. This research provides a comprehensive analysis of how fictional works can reshape our perceptions of historical reality.